2011
DOI: 10.2478/v10152-010-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Unsatisfactory cardiovascular risk control - opportunities for family medicine

Abstract: Although theoretically very effective and apparently quite straightforward, cardiovascular prevention leaves much to be desired in practice. Several reasons, including ethical, conceptual, psychological, and Klju~ne besede: sr~no-`ilne bolezni, prepre~evanje, dru`inska medicina Zdrav Var 20; 50: 75-8 doi 0.2478/v052-00-0030-9 Medical research has markedly improved the knowledge of etiology and prevention of cardiovascular conditions, particularly coronary heart disease (CHD), so that these disorders coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…It has already been observed that family physicians in Croatia had positive attitude toward science, but only 6% published an article in a PubMed-indexed journal (22). At 4 medical schools in Croatia, a total of 61 faculty members in the Departments of Family Medicine in 2007 published 316 scientific and professional articles and a half of them had research degrees (25). However, family medicine faculty comprises only 2% of family physicians in Croatia and they are not representative of family medicine practitioners in Croatia.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been observed that family physicians in Croatia had positive attitude toward science, but only 6% published an article in a PubMed-indexed journal (22). At 4 medical schools in Croatia, a total of 61 faculty members in the Departments of Family Medicine in 2007 published 316 scientific and professional articles and a half of them had research degrees (25). However, family medicine faculty comprises only 2% of family physicians in Croatia and they are not representative of family medicine practitioners in Croatia.…”
Section: Discussionmentioning
confidence: 99%
“…Goodman et al [11] noticed that the key challenge is identification of structural heart disease and inheritable conditions that increase incidence for lethal arrhythmias during exercise, because sudden cardiac events often occur without any warning or prediction. Therefore, early detection of persons with higher risk for sudden cardiac death is of crucial importance [12]. In this regard, numerous European countries have introduced a mandatory medical examination for all persons registered in sports clubs or associations.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a nurse practitioner to a family physician's team offers the opportunity for interprofessional teamwork aimed at a higher quality of patient care. In many European countries, nurse practitioners have already been introduced to primary care teams to improve quality of care and to reduce healthcare costs (Dierick-van Daele, Metsemakers, Derckx, Spreeuwenberg, & Vrijhoef, 2009;Klemenc-Ketis, Terbovc, Gomiscek, & Kersnik, 2015;Petek & Mlakar, 2016;Rumboldt, Kuzmanic, Petric, & Rumboldt, 2011;Svab, Petek-Ster, Kersnik, Zivcec-Kalan, & Car, 2005). It has been shown that nurse practitioners can even achieve similar health outcomes to family physicians themselves (Dierick-van Daele et al, 2009;Laurant et al, 2008;Voogdt-Pruis, Beusmans, Gorgels, Kester, & Van Ree, 2010).…”
Section: Introductionmentioning
confidence: 99%